Analysis Of The Acceptance Of Robo-Advisor Technology As A Support For Investment Activities Among Generation Z - Putera, Bayu Ardiansyah (Reviu Akuntansi, Keuangan, dan Sistem Informasi, 2025)
This study aims to analyze the factors that influence the behavioral intention of Generation Z (Gen Z) in Indonesia to use robo-advisors as a technological support for their investment activities. The independent variables in this study are perceived usefulness, perceived ease of use, and attitude toward using, as derived from the Technology Acceptance Model (TAM), while the dependent variable is behavioral intention to use. The results of the multiple linear regression analysis indicate that the three independent variables collectively have a significant effect on the behavioral intention to use robo-advisors. In addition, perceived usefulness, perceived ease of use, and attitude toward using each have a positive and significant effect individually. These findings suggest that perceptions of usefulness, ease of use, and positive attitudes toward technology are key determinants of robo-advisor adoption among Gen Z. The results also serve as a reference for digital investment platform developers in designing adaptive, value-added, and user-friendly systems for the younger generation.